Formación docente : un camino en la búsqueda de reflexiones en torno a las prácticas evaluativas en la IED Ricardo Hinestrosa Daza de la Vega (2017)
The evaluation of learning is perhaps one of the most sensitive issues in teaching, as it is one of the most discussed and controversial aspects of teaching. This is due, among other things, to the multiple approaches, visions and conceptions that we have of it and that clearly constitutes a factor that denotes certain weaknesses within our formation. The evaluation of learning in spite of its importance and the daily life with which it is carried out, is a subject on which little reflection and in-depth debate takes place. Most of the discussions surrounding the evaluation focus on the analysis of the results students obtain and not on what, how or what to evaluate. Taking into account the above, this research work sought to generate a space for teacher training around the issue of formative evaluation, its challenges and its implications, where through the creation of a learning community with secondary school teachers...